Deprescribing in older patients by early‐career general practitioners: Prevalence and associations. Issue 8 (24th May 2021) - Magin, Parker; Quain, Debbie; Tapley, Amanda; van Driel, Mieke; Davey, Andrew; Holliday, Elizabeth; Ball, Jean; Kaniah, Ashwin; Turner, Rachel; Spike, Neil; FitzGerald, Kristen; Hilmer, Sarah
Abstract: Rationale and aims: Deprescribing is the health‐professional‐supervised process of withdrawal of an inappropriate medication to manage polypharmacy and improve patient outcomes. Given the harms of polypharmacy and associated inappropriate medicines, practitioners, especially general practitioners (GPs), are encouraged to take a proactive role in deprescribing in older patients. While trial evidence for benefits of deprescribing is accumulating, there is currently little epidemiologic evidence of clinicians' (including GPs') deprescribing behaviours. We aimed to establish the prevalence and explore associations of deprescribing of inappropriate medicines by early‐career GPs. Methods: A cross‐sectional analysis of the ReCEnT study of GP registrars' in‐consultation experience, 2016‐18. Participants recorded 60 consecutive consultations, three times at 6‐month intervals, including medicines ceased (our measure of deprescribing). The outcome was deprescribing of an inappropriate medicine (defined by a synthesis of three accepted classification systems) in patients 65 years or older. Logistic regression determined the associations of deprescribing inappropriate medicines. Results: One thousand one hundred and thirteen registrars reported 19 581 consultations with patients 65 years and older. Inappropriate medicines were deprescribed in 2.6% (95% CIs 2.4%‐2.9%) of consultations. Of deprescribed medicines, 43% had been prescribed for three months or longer. Most commonly deprescribed were opioids (19%), proton pump inhibitors (9.2%), anti‐inflammatory drugs (9.0%), statins (7.8%), and antidepressants (6.6%). The most common reason for deprescribing was: "no longer indicated" (38%). Significant adjusted associations of deprescribing included patients identifying as Aboriginal or Torres Strait Islander (OR 2.86); continuity‐of‐care (ORs 0.71 and 0.20 for the patient being new to practice and to the registrar, respectively); inner‐regional compared to major‐city location (OR 1.33); the problem/diagnosis being chronic (OR 1.90); and longer consultations (OR 1.03 per minute increase in duration). Conclusion: These findings will have important implications for the education of GPs in deprescribing as a clinical skill.